Lake biodiversity conservation : impact & benefit for human / Afiq Daniel Azahar and Helmi hamzah - Azahar, Afiq Daniel; Hamzah, Helmi (2024)
Lakes have an important role in human life and ecosystems and the importance of preserving freshwater lakes cannot be disputed. Lake gives benefit to create positive social, culture and physical development in community and It highlights the interconnection between human activities and environmental health. However, the conservation of the lake is still not comprehensive where there is still a lack of awareness or enforcement to the environment of lake.The method of research is using quantitative methods research which using quantitative data research is focuses on gathering non- numerical data to gain insights into people's attitudes, perceptions, behaviors, and experiences on lake. Tasik Iskandar faces litter and pollution issues due to weak enforcement. Visitor opinions on cleanliness vary, but most enjoy the lake. The study recommends better enforcement, cleanliness measures, and infrastructure. Collaboration between authorities and the public is crucial for the lake's well-being. These finding can be a powerful tool for assessing the impact of conservation efforts and guiding future initiatives to protect these valuable ecosystems. This will help preserve or improve the Lake area to be a better Picnic spot for the local community.